Use of platelet glycoprotein IIb/IIIa inhibitors in diabetics undergoing PCI for non-ST-segment elevation acute coronary syndromes: impact of clinical status and procedural characteristics - Bauer, Timm; Möllmann, Helge; Weidinger, Franz; Zeymer, Uwe; Seabra-Gomes, Ricardo; Eberli, Franz R.; Serruys, Patrick W.; Vahanian, Alec; Silber, Sigmund; Wijns, William; Hochadel, Matthias; Nef, Holger M.; et al. (Clinical research in cardiology, 2010)
BACKGROUND: The most recent ESC guidelines for percutaneous coronary intervention (PCI) recommend the use of glycoprotein IIb/IIIa inhibitors (GPI) in high risk patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS), particularly in diabetics. Little is known about the adherence to these guidelines within Europe. - METHODS AND RESULTS: Between May 2005 and April 2008 a total of 47,407 consecutive patients undergoing PCI were prospectively enrolled into the PCI-Registry of the Euro Heart Survey Programme. In the present analysis we examined the use of GPI in 2,922 diabetics who underwent PCI for NSTE-ACS. In this high risk population only 22.2% received a GPI; 8.9% upstream and 13.4% during PCI. The strategy of the individual institution had a major impact on the usage of GPI. In the multiple regression analysis clinical instability and complex lesion characteristics were strong independent determinants for the use of GPI, whereas renal insufficiency was negatively associated with its use. After adjustment for confounding variables no significant differences in hospital mortality could be observed between the cohorts, but a significantly higher rate of non-fatal postprocedural myocardial infarction was observed among patients receiving GPI upstream. - CONCLUSIONS: Despite the recommendation for its use in the current ESC guidelines, only a minority of the diabetics in Europe undergoing PCI for NSTE-ACS received a GPI. The use of GPI was mainly triggered by high-risk interventional scenarios.
Gesehen am 15.12.2022